L'impact réel des technologies de l'information et de la communication sur la forme scolaire - Pierre-François Coen (Nantes Université, 2011)
New technologies have fundamentally changed the present world. The generalized use of computers and in particular Internet has not only modified the relations between people but also their behavior towards information and knowledge. School also takes part in this process and a lot of countries have organized numerous programs to integrate ICT into education. This ICT integration requires modifying teaching practices and the organization of formal education. This paper deals with the real impact of ICT on several dimensions of the organization of formal education such as knowledge and its mediation, learning in these new environments, roles of education actors as well as transformations of teaching-learning devices.